Associação da doença do refluxo gastroesofágico e da úlcera péptica em adultos e o desenvolvimento de alterações periodontais e cárie dentária:revisão sistemática e meta-análise - Maria Cláudia Alves (2023)
Objectives: to evaluate the relationship between gastroesophageal reflux disease and/or peptic ulcer disease, and caries lesions and/or periodontal disease. Methods: The present study was carried out in accordance with the PRISMA (Key Items for Reporting Systematic Reviews and Meta-Analyses) guidelines and was registered (CRD42023386741) on the Prospero Platform (International Prospective Registry of Systematic Reviews, University of York, York, United Kingdom United). For this purpose, the research was conducted in four databases (PubMed, WebOfScience, Embase and Scopus), in addition to gray literature, without restrictions on language or publication date. Of the 1719 studies selected, 165 were subjected to text analysis. Sixteen studies were eligible (15 cross-sectional and one case-control study), and 7 studies were entered into the meta-analysis. Results: It was possible to verify a difference in the means between gastroesophageal reflux disease and PMA Index (OR 1.00, 95% CI 0.60; 1.40), in this meta-analysis I2 = 53%. There was also a difference in the means between Gastroesophageal Reflux Disease and OHI Index – S (OR 1.22, 95% CI 0.50; 1.93), in this meta-analysis I2 = 84%. There is no association between GERD and DMFT (DM = 0.53; 95% CI = -1.39; 2.45), in this meta-analysis I2 = 84% and between GERD and % DMFT (DM = -0.87; 95% CI = -19.31; 17.56), in this meta-analysis I2 = 90%. There was also no association between GERD and IPV (MD = 0.23; 95% CI = -0.04; 0.51), in this meta-analysis I2 = 0%. Finally, there was no association between peptic ulcer disease and bone loss (OR = 1.22; 95% CI = 0.43; 3.40), in this meta-analysis I2 = 90%. Conclusion: according to the systematic review, individuals with gastroesophageal reflux disease and peptic ulcers were more likely to have periodontal disease and caries lesions, compared to individuals without these systemic impairments.